EFFECT OF BODY CONDITION SCORE OF HAMDANI AND KARADI EWES ON THEIR REPRODUCTIVE AND MEAT PRODUCTIVITY OF THEIR LAMBS - Imad Al-Deen M. Dahal (Mesopotamia Journal of Agriculture)
Eighty five Hamdani (H) and 41 Karadi (K) ewes were included in four body condition score (BCS) groups, to study the effect of ewe BCS at tapping on their fertility, lambing percentage, milk production, lamb weights, carcase weight and meat production and their financial returns. Ewes were fed 400g /day/head of concentrate ration which increased to 1 kg/day/head during lactating season. Lambs were on concentrate free feeding from weaning to slaughter. Ewes in BCS3 were found to have significant (p< 0.05) superiority than those in BCS1 and 4 in fertility percentage and than both breed ewes in BCS1 and K ewes in BCS4 in lambing percentage . The significant (p< 0.05) high milk production of the two breed ewes in BCS3 hence for significant (p< 0.05) heavier lamb weaning weight and ADG for H and K breed when compared to those in BCS1 and BCS2 .BCS3 group drew a head of others in weaning percentage and lamb weaning weight to original ewe number ratio for H and K breed. While the lower recoreds were observed for both breed lambs in BCS1 . H and K lambs in BCS3 last 145 and 162.5 days to slaughter which were significantly (p<0.05) shorter than those 200.7 , zero days of both breeds in BCS1 respectively. Carcase weight of H and K lambs in BCS3 and BCS1 were 13.8, 13.3 kg and 11.8, zero kg respectively. While carcase weight to original H and K ewe number ratio in BCS3 and BCS1 was found to be 12.4, 11.8 and 5.1, 0.0 respectively. So the financial returns of the BCS1,2,3 and 4 could be summarize 61200, 93600 ,148800 and 109200 ID for the H breed and 0.0, 106800, 141600 and 72000 ID for K breed respectively.